Muslim Female Adolescents’ Value Orientation and Perspectives on Clothing Choices in the Context of Islamic Religious Education - Salman Ahyani; Abdul Karim Panjaitan; Zaitun Khairani; Sabar Hati Albanjari; Feri Irwansyah Marpaung; Syafawi Ahmad Qadzafi (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
Muslim female adolescents’ clothing choices are increasingly shaped by social media and global culture, creating a gap between religious teachings and everyday dress practices. This study examines the value orientations underlying Muslim female adolescents’Muslim female adolescents’ clothing choices and the role of Islamic Religious Education (PAI) in addressing this gap. Using a qualitative approach in Silo Lama Village, data were gathered from fifteen Muslim female adolescents through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal three dominant value orientations: social-aesthetic, social-conformity, and religious-obedience. For most participants, dress functions as a symbol of identity rather than a full internalization of Islamic values, influenced by social media, peer acceptance, and weak religious internalization. The study recommends strengthening Islamic Religious Education through integrative and contextual approaches, supported by family involvement and a conducive social environment, to nurture sustainable awareness and practice of Islamic dress values.